2020
DOI: 10.3389/fncel.2020.00036
|View full text |Cite
|
Sign up to set email alerts
|

Depolarizing GABA Transmission Restrains Activity-Dependent Glutamatergic Synapse Formation in the Developing Hippocampal Circuit

Abstract: γ-Aminobutyric acid (GABA) is the main inhibitory neurotransmitter in the mature brain but has the paradoxical property of depolarizing neurons during early development. Depolarization provided by GABA A transmission during this early phase regulates neural stem cell proliferation, neural migration, neurite outgrowth, synapse formation, and circuit refinement, making GABA a key factor in neural circuit development. Importantly, depending on the context, depolarizing GABA A transmission can either drive neural … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 88 publications
(130 reference statements)
7
17
0
Order By: Relevance
“…In the same paper, it was suggested that ketamine-dependent inhibition of Ca 2+ transients in immature neurons may be co-mediated by GABA A receptor. In contrast to the adult brain, in the developing hippocampus, GABA acts as excitatory neurotransmitter and depolarizes developing pyramidal neurons through GABA A receptor [52]. At this stage of development, GABA A receptor inhibition should lead to suppression of spontaneous Ca 2+ transients.…”
Section: Ketamine and Calcium Oscillationsmentioning
confidence: 99%
“…In the same paper, it was suggested that ketamine-dependent inhibition of Ca 2+ transients in immature neurons may be co-mediated by GABA A receptor. In contrast to the adult brain, in the developing hippocampus, GABA acts as excitatory neurotransmitter and depolarizes developing pyramidal neurons through GABA A receptor [52]. At this stage of development, GABA A receptor inhibition should lead to suppression of spontaneous Ca 2+ transients.…”
Section: Ketamine and Calcium Oscillationsmentioning
confidence: 99%
“…Studies have demonstrated that the application of GABAA antagonists to organotypic hippocampal neuronal cultures showed marked loss of spines. Upon administration of bicuculline, a GABAA receptor antagonist decreased spine density, explains that absence of hyperpolarizing GABAA transmission resulted in the spine loss [ 76 ]. Activation of GABA receptors suppressed overall cytosolic calcium concentration promoting spine shrinkage and elimination in CA1 region of rat hippocampus.…”
Section: Effects Of Pharmacological Interventions On Dendritic Spinesmentioning
confidence: 99%
“…As the brain matures, upregulation of the KCC2 transporter lowers the intracellular chloride concentration, driving GABA A -mediated hyperpolarization (Rivera et al, 1999;Khirug et al, 2005;Ben-Ari et al, 2007Tyzio et al, 2008). This shift in GABAergic transmission plays an important role in the development of hippocampal circuit formation (Leinekugel et al, 1995;Ben-Ari et al, 1997;Cancedda et al, 2007;Wang and Kriegstein, 2008;Kirmse et al, 2015;Oh et al, 2016;Valeeva et al, 2016;Brady et al, 2018;Salmon et al, 2020), and its disruption is implicated in neurodevelopmental disorders (Deidda et al, 2014).…”
Section: Gabaergic Signalingmentioning
confidence: 99%